Disease variants in genomes of 44 centenarians. Issue 5 (15th June 2014) - Freudenberg‐Hua, Yun; Freudenberg, Jan; Vacic, Vladimir; Abhyankar, Avinash; Emde, Anne‐Katrin; Ben‐Avraham, Danny; Barzilai, Nir; Oschwald, Dayna; Christen, Erika; Koppel, Jeremy; Greenwald, Blaine; Darnell, Robert B.; et al.
Abstract To identify previously reported disease mutations that are compatible with extraordinary longevity, we screened the coding regions of the genomes of 44 Ashkenazi Jewish centenarians. Individual genome sequences were generated with 30× coverage on the Illumina HiSeq 2000 and single‐nucleotide variants were called with the genome analysis toolkit (GATK). We identified 130 coding variants that were annotated as "pathogenic" or "likely pathogenic" based on the ClinVar database and that are infrequent in the general population. These variants were previously reported to cause a wide range of degenerative, neoplastic, and cardiac diseases with autosomal dominant, autosomal recessive, and X‐linked inheritance. Several of these variants are located in genes that harbor actionable incidental findings, according to the recommendations of the American College of Medical Genetics. In addition, we found risk variants for late‐onset neurodegenerative diseases, such as the APOE ε4 allele that was even present in a homozygous state in one centenarian who did not develop Alzheimer's disease. Our data demonstrate that the incidental finding of certain reported disease variants in an individual genome may not preclude an extraordinarily long life. When the observed variants are encountered in the context of clinical sequencing, it is thus important to exercise caution in justifying clinical decisions.